Prevalência de anticorpos anti-Neospora caninum, anti toxoplasma gondii e anti-leptospira spp. e resposta vacinal para Leptospira spp. em rebanho ovino no município de Uberlândia, MG - Moreira, Rafael Quirino (2009)
The objectives were: to determine the seroprevalence of Neospora caninum, Toxoplasma gondii and Leptospira spp; monitor the prevalence of Leptospira spp. within 10 months and assess the profile of agglutinins induced seroconversion of two multi-purpose bacterins in sheep flock with reported reproductive losses in Uberlândia, MG. We collected blood samples from 98 sheep. The samples were tested against the ELISA for Neospora caninum and Toxoplasma gondii and the method of microscopic agglutination test (MAT) for Leptospira spp. After ten months was held a second crop of 101 sheep, serum samples were subjected to SAM to monitor the prevalence of Leptospira spp. the herd. Fifty nine animals were divided into six experimental groups: positive for the SAM immunized with commercial vaccine (group I) and autologous (group III), and negative immunized with commercial vaccine (group II) and autologous (group IV), and a group of positive animal for SAM not vaccinated (V) and negative sheep for the SAM unvaccinated (group VI). The levels of agglutinins were evaluated and the antibody titers achieved in series of dilutions in the ratio of two (1:100, 1:200, 1:400, 1:800, 1:1600, 1:3200). Considerable prevalence of 30.6%, 63.3% and 23.46% for N. caninum, T. gondii and Leptospira spp., respectively, was attested. The greater prevalence of Leptospira spp. occurred at the time of onset of reproductive bouts (23%) tend to fall ten months after the first harvest (13.86%). The vaccine response obtained was heterogeneous in the proportion of reacting animals and levels of agglutinating antibodies against the serovars included in the formulation of vaccines. Titers achieved were for Harjo and Wollf at dilutions of 1:200. The range of best seroconversion occurred between 30 and 120 days after vaccination cousin.